A CO2 flooding sealing and in-situ solidification integrated system and preparation method thereof

By introducing an integrated system into CO2 oil-fighting and sealing technology, the second-order curing mechanism is used to promote the formation of calcium carbonate microcrystals, the problem of slow CO2 storage speed is solved, and the dual effects of CO2 oil-fighting and anti-spraying and in-situ mineralization and storage burial are achieved, which improves CO2 oil-fighting efficiency and storage safety.

CN119331593BActive Publication Date: 2025-03-14CHENGDU UNIVERSITY OF TECHNOLOGY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411885435.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-14
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

The existing CO2 oil-fighting and sealing technology in the reservoir is slow to store, which has the risk of leakage, and it is difficult to achieve CO2 oil-fighting and prevent it from being discharged and mineralized in situ at the same time.

Method used

The integrated system of CO2 oil-fighting sealing and in-situ curing is adopted. The system consists of foaming agent, foaming synergist, stabilizer, first-order curing agent, second-order curing agent, etc. It promotes the formation of calcium carbonate microcrystals through the second-order curing mechanism and accelerates the mineralization sealing rate.

Benefits of technology

The dual role of CO2 oil-fighting and anti-blasting and in-situ mineralization storage is realized, and the CO2 oil-fighting efficiency and the safety of long-term storage of CO2 in underground reservoirs is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119331593B_ABST
    Figure CN119331593B_ABST
Patent Text Reader

Abstract

The invention discloses an integrated system for sealing and in-situ curing of CO2 oil flooding and a preparation method thereof, and belongs to the field of oilfield chemical technology. The system is made of the following raw material components in weight percentage: 0.05% to 0.10% of a foaming agent, 0.1% to 0.5% of a foaming synergist, 0.1% to 0.8% of a stabilizer, 0.15% to 0.30% of a first-order curing agent A, 0.25% to 0.35% of a first-order curing agent B, 1.0% to 2.0% of a second-order curing agent, and the rest is water. The first-order curing agent A is resorcinol or hydroquinone; the first-order curing agent B is urotropine; and the second-order curing agent is a choline chloride deep eutectic solvent. The integrated system of CO2 oil flooding sealing and in-situ curing of the present invention adopts a unique second-order curing mechanism, which suppresses CO2 cross-flow while relying on the cross-linking of the stabilizer and the first-order curing agent to form a foam gel to achieve first-order curing, and then promotes the formation of calcium carbonate microcrystals under the ion exchange action of the second-order curing agent, accelerates the mineralization sealing rate, and forms a final solidified product.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of oilfield chemistry, in particular to a CO2 oil flooding sealing and in-situ solidification integrated system and a preparation method thereof. Background Art

[0002] CO2 capture, oil recovery and storage (CCUS-EOR) technology can achieve the dual purpose of enhancing oil recovery and geological storage of CO2. However, due to the difference in viscosity between the oil and gas phases and the heterogeneity of the reservoir, gas channeling is very likely to occur during the CO2 flooding process, thereby reducing the overall sweep efficiency and ultimate recovery. In addition, although CO2 storage in oil reservoirs has great potential, after storage, CO2 is still stored in the formation in a free state for a long time, which poses a risk of leakage.

[0003] Existing CO2 oil flooding sealing technologies are mainly based on blocking the dominant channels, and common sealing systems are gel, foam and CO2 responsive materials. For example, patent CN107556996B discloses a CO2 responsive in-situ gel sealing agent and its preparation method and application. The gel system is composed of a cross-linking agent and a hydrophobically modified polyacrylamide polymer compounded with polyamine compounds and phenolic compounds. The gel system can undergo a cross-linking reaction in an oil reservoir environment where CO2 exists, forming a cross-linked polymer gel with good flexibility and stable performance, and effectively blocking the gas channel. Patent CN111139051B discloses a foam sealing agent for CO2 flooding in heavy oil reservoirs and its preparation method and application. The foam system is composed of α-olefin sulfonate, quaternary ammonium salt imidazoline, hydroxyethyl cellulose, Na5P3O 10 The foam sealing agent for CO2 flooding has a simple process, a long half-life, a good foam effect and corrosion inhibition performance, which can effectively control CO2 gas channeling and mobility and improve oil recovery efficiency. However, these existing CO2 sealing methods have no effect on promoting the storage of CO2 in oil reservoirs.

[0004] There are a variety of storage mechanisms in the process of CO2 reservoir storage. In the short term, physical storage mechanisms such as structural storage and residual storage are the main ones. However, from the perspective of long-term safety, the mineralization storage mechanism is more ideal. However, due to the slow mass transfer of CO2 to the water phase and the long kinetic process of mineral dissolution and carbonate crystal growth, the mineralization storage rate is slow and the human controllability is poor. Some studies have shown that under natural conditions, the mineralization storage volume is only 2% within 100 years after CO2 is injected into the formation. Therefore, after CO2 is injected into the reservoir, it is still highly dependent on the integrity of the formation, there are safety hazards, and long-term monitoring of the formation is required. The subsequent maintenance cost is high and the time is long. Therefore, from the dual purpose of CO2 flooding and geological storage, it is urgent to integrate the two needs to develop new technologies that can simultaneously achieve CO2 sealing and in-situ mineralization storage. Summary of the invention

[0005] In view of the problem of slow geological storage speed of CO2 injected into the formation in the current CCUS-EOR technology, the present invention provides an integrated system of CO2 oil flooding anti-channeling and in-situ solidification. The system has the dual functions of CO2 oil flooding anti-channeling and in-situ mineralization storage of CO2.

[0006] The CO2 oil flooding sealing and in-situ solidification integrated system provided by the present invention is made of the following raw material components in weight percentage:

[0007] 0.05%~0.10% foaming agent, 0.1%~0.5% foaming synergist, 0.1%~0.8% stabilizer, 0.15%~0.30% first-stage curing agent A, 0.25%~0.35% first-stage curing agent B, 1.0%~2.0% second-stage curing agent, and the rest is water. The total of all components is 100%.

[0008] Wherein, the foaming agent is one or a combination of sodium alkylbenzene sulfonate and sodium dodecyl sulfate.

[0009] The foaming synergist is amphiphilic carbon quantum dots; the amphiphilic carbon quantum dots are prepared by the following method:

[0010] (1) Mix dodecylamine and citric acid and stir at 180°C for 5 h.

[0011] (2) dissolving the product of step (1) in anhydrous ethanol, centrifuging and removing insoluble matter in the product;

[0012] (3) The product was dissolved in deionized water, dialyzed using a 1 kDa dialysis membrane for 12 h, and finally freeze-dried to obtain amphiphilic carbon quantum dots.

[0013] The stabilizer is a copolymer of acrylamide and sodium 2-acrylamide-2-methylpropane sulfonate, and the molecular weight of the copolymer is 1 million to 8 million. The molar ratio of acrylamide to sodium 2-acrylamide-2-methylpropane sulfonate is preferably 7:1 to 18:1. The preparation method of the copolymer is as follows:

[0014] Acrylamide and sodium 2-acrylamido-2-methylpropanesulfonate are dissolved in water according to a preferred molar ratio, and then an appropriate amount of sodium hydroxide is added to adjust the pH value of the solution to neutral. An appropriate amount of ammonium persulfate is added to the solution to fully dissolve, and the reaction is carried out at a constant temperature of 60°C for 4 hours. The product is taken out, dried, and crushed to obtain a powder product. Among them, the total mass of acrylamide and sodium 2-acrylamido-2-methylpropanesulfonate accounts for 20% of the total mass fraction of the reaction system, and the amount of ammonium persulfate accounts for 0.05% to 0.1% of the total mass of acrylamide and sodium 2-acrylamido-2-methylpropanesulfonate.

[0015] The first-stage curing agent A is resorcinol or hydroquinone.

[0016] The first-stage curing agent B is hexamethylenetetramine.

[0017] The second-stage curing agent is a choline chloride deep eutectic solvent.

[0018] Preferably, the second-stage curing agent is a combination of choline chloride and urea, and based on 100% of the total amount of choline chloride and urea, the mass percentage of choline chloride is 30% to 50%, and the mass percentage of urea is 50% to 70%.

[0019] The preparation method of the CO2 oil flooding sealing and in-situ curing integrated system is as follows:

[0020] (1) Dissolving the stabilizer in water to form a stabilizer solution;

[0021] (2) dissolving the second-stage curing agent in another portion of water to form a second-stage curing agent solution;

[0022] (3) The stabilizer solution, the second-stage curing agent solution, the foaming agent, the foaming synergist, the first-stage curing agent A, the first-stage curing agent B and the remaining water are mixed and slowly stirred at a speed of 8-12 r / min for 8-10 minutes to form a sealing and carbon fixation solution, which is an integrated system of CO2 oil flooding sealing and in-situ curing.

[0023] The application method of the CO2 oil flooding anti-channeling and in-situ solidification integrated system is to alternately inject the CO2 oil flooding anti-channeling and in-situ solidification integrated system (i.e., anti-channeling carbon fixation solution) and CO2 into the reservoir. The integrated system has the dual functions of CO2 oil flooding anti-channeling and in-situ mineralization and storage of CO2.

[0024] Compared with the prior art, the present invention is beneficial in that:

[0025] (1) The integrated system of CO2 oil flooding sealing and in-situ curing of the present invention adopts a unique second-order curing mechanism, which suppresses CO2 cross-flow while relying on the cross-linking of the stabilizer and the first-order curing agent to form a foam gel to achieve first-order curing. Subsequently, under the ion exchange effect of the second-order curing agent, the formation of calcium carbonate microcrystals is promoted, the mineralization sealing rate is accelerated, the second-order curing is achieved, and the final solidified product is formed.

[0026] (2) The integrated system of CO2 oil flooding prevention and in-situ solidification of the present invention has the dual functions of CO2 oil flooding prevention and in-situ mineralization and storage of CO2. It can increase the volume swept by CO2 displacement while accelerating the mineralization and storage of CO2, thereby improving the CO2 oil flooding efficiency and the safety of long-term storage of CO2 in underground oil reservoirs.

[0027] Other advantages, objectives and features of the present invention will be embodied in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 It is a schematic diagram of the second-order solidification mechanism of the integrated system of CO2 oil flooding sealing and in-situ solidification of the present invention.

[0029] Figure 2 A schematic diagram of a physical model of artificial sand-filled pipe displacement for indoor displacement experiments using the CO2 oil flooding sealing and in-situ solidification integrated system of the present invention. DETAILED DESCRIPTION

[0030] The preferred embodiments of the present invention are described below in conjunction with the accompanying drawings. It should be understood that the preferred embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0031] The second-order curing mechanism of the integrated system of CO2 flooding sealing and in-situ curing of the present invention is as follows: Figure 1 As shown. After the CO2 flooding sealing and in-situ solidification integrated system (i.e. sealing and solidifying carbon solution) and CO2 are alternately injected into the reservoir, the foaming agent and foaming synergist promote the gradual formation of CO2 foam between water and CO2 under the shearing action. At the same time, the amphiphilic carbon quantum dots rich in amino and carboxyl hydrophilic groups and hydrophobic long carbon chains are adsorbed on the gas-liquid interface film to form a nanoparticle protective layer, which enhances the mechanical strength of the liquid film, greatly improves the foam stability, inhibits CO2 cross-flow and expands the CO2 swept volume. After the foam migrates to the deep formation, the first-order curing agent plays a role, cross-links the stabilizer to form a gel foam structure and gradually stops migration. CO2 is bound in the gel in the form of foam and cannot migrate, forming a preliminary solidification; then the second-order curing agent diffuses and migrates in the water of the gel network, undergoes ion exchange with the formation water, and gradually introduces the calcium ions in the formation water into the gel network, which contacts with a small amount of carbonate ions formed by the CO2 molecules dissolved in the bound water in the gel network, forming calcium carbonate microcrystals and gradually growing. As the carbonate ions in the bound water in the gel network are gradually consumed, the CO2 in the gel foam dissolves again into the bound water in the gel network; at the same time, the rock surface in contact with the gel foam is continuously corroded by the carbonic acid dissolved in the gel network and new calcium ions are formed, which enter the gel network under the ion transfer action of the secondary curing agent and form calcium carbonate. This cycle repeats itself, and the CO2 in the gel foam gradually turns into calcium carbonate and is stored in the gel network, completing mineralization and storage.

[0032] The foaming synergist amphiphilic carbon quantum dots used in the following examples and comparative examples are prepared by the following specific method:

[0033] (1) Mix 4 g of dodecylamine and 4 g of citric acid, and stir at 180°C and 100 r / min for 5 h;

[0034] (2) dissolving the product of step (1) in 100 mL of anhydrous ethanol and centrifuging at 1000 r / min for 15 min to remove insoluble matter in the product;

[0035] (3) The product was dissolved in 100 mL of deionized water, dialyzed with a 1 kDa dialysis membrane for 12 h, and finally freeze-dried to obtain the target amphiphilic carbon quantum dots.

[0036] Example 1

[0037] A CO2 flooding sealing and in-situ solidification integrated system, the preparation method is as follows:

[0038] (1) Add 8 g of stabilizer into 92 g of water and keep mechanical stirring at 500 r / min for 6 hours to form a stabilizer solution; the stabilizer is prepared by polymerization of acrylamide and sodium 2-acrylamido-2-methylpropanesulfonate in a molar ratio of 7:1.

[0039] (2) Add 3 g of choline chloride and 7 g of urea into 90 g of water, maintain mechanical stirring at 500 r / min, and stir for 10 min to obtain a second-stage curing agent solution;

[0040] (3) 10 g of stabilizer solution, 20 g of second-stage curing agent solution, 0.1 g of sodium dodecylbenzene sulfonate foaming agent, 0.5 g of amphiphilic carbon quantum dot foaming enhancer, 0.3 g of resorcinol first-stage curing agent A, 0.35 g of urotropine first-stage curing agent B and 68.75 g of water were mixed, and mechanically stirred slowly at 10 r / min for 10 min to form a sealing and carbon-fixing solution, which is the integrated system 1 of CO2 oil flooding sealing and in-situ curing.

[0041] Example 2

[0042] A CO2 flooding sealing and in-situ solidification integrated system, the preparation method is as follows:

[0043] (1) Add 8g of stabilizer to 92g of water, maintain mechanical stirring at 500r / min, and stir for 6h to form a stabilizer solution. The stabilizer is polymerized by acrylamide and sodium 2-acrylamido-2-methylpropanesulfonate in a molar ratio of 7:1.

[0044] (2) Add 3 g of choline chloride and 7 g of urea into 90 g of water, maintain mechanical stirring at 500 r / min, and stir for 10 min to obtain a second-stage curing agent solution;

[0045] (3) Mix 10 g of stabilizer solution, 20 g of second-stage curing agent solution, 0.1 g of sodium dodecyl sulfate foaming agent, 0.5 g of amphiphilic carbon quantum dot foaming enhancer, 0.25 g of hydroquinone first-stage curing agent A, 0.35 g of urotropine first-stage curing agent B and 68.80 g of water, and stir slowly at 10 r / min for 10 min to form a sealing and carbon fixation solution, which is the integrated system 2 of CO2 oil flooding sealing and in-situ curing.

[0046] Example 3

[0047] A CO2 flooding sealing and in-situ solidification integrated system, the preparation method is as follows:

[0048] (1) Add 4g of stabilizer to 96g of water, maintain mechanical stirring at 500r / min, and stir for 6h to form a stabilizer solution. The stabilizer is polymerized by acrylamide and sodium 2-acrylamido-2-methylpropanesulfonate in a molar ratio of 10:1.

[0049] (2) Add 4 g of choline chloride and 6 g of urea into 90 g of water, maintain mechanical stirring at 500 r / min, and stir for 10 min to obtain a second-stage curing agent solution;

[0050] (3) Mix 10 g of stabilizer solution, 15 g of second-stage curing agent solution, 0.05 g of sodium dodecylbenzene sulfonate foaming agent, 0.3 g of amphiphilic carbon quantum dot foaming enhancer, 0.2 g of hydroquinone first-stage curing agent A, 0.3 g of urotropine first-stage curing agent B and 74.15 g of water, and stir slowly at 10 r / min for 10 min to form a sealing and carbon fixation solution, which is the integrated system of CO2 oil flooding sealing and in-situ curing 3.

[0051] Example 4

[0052] A CO2 flooding sealing and in-situ solidification integrated system, the preparation method is as follows:

[0053] (1) Add 4g of stabilizer to 96g of water, maintain mechanical stirring at 500r / min, and stir for 6h to form a stabilizer solution. The stabilizer is polymerized by acrylamide and sodium 2-acrylamido-2-methylpropanesulfonate in a molar ratio of 10:1.

[0054] (2) Add 4 g of choline chloride and 6 g of urea into 90 g of water, maintain mechanical stirring at 500 r / min, and stir for 10 min to obtain a second-stage curing agent solution;

[0055] (3) Mix 10 g of stabilizer solution, 15 g of second-stage curing agent solution, 0.05 g of sodium dodecyl sulfate foaming agent, 0.3 g of amphiphilic carbon quantum dot foaming enhancer, 0.25 g of resorcinol first-stage curing agent A, 0.3 g of urotropine first-stage curing agent B and 74.1 g of water, and stir slowly at 10 r / min for 10 min to form a sealing and carbon-fixing solution, which is the integrated system of CO2 oil flooding sealing and in-situ curing 4.

[0056] Example 5

[0057] A CO2 flooding sealing and in-situ solidification integrated system, the preparation method is as follows:

[0058] (1) Add 4g of stabilizer to 96g of water, maintain mechanical stirring at 500r / min, and stir for 6h to form a stabilizer solution. The stabilizer is polymerized by acrylamide and sodium 2-acrylamido-2-methylpropanesulfonate in a molar ratio of 10:1.

[0059] (2) Add 4 g of choline chloride and 6 g of urea into 90 g of water, maintain mechanical stirring at 500 r / min, and stir for 10 min to obtain a second-stage curing agent solution;

[0060] (3) Mix 10 g of stabilizer solution, 15 g of second-stage curing agent solution, 0.05 g of sodium dodecyl sulfate foaming agent, 0.1 g of amphiphilic carbon quantum dot foaming enhancer, 0.25 g of resorcinol first-stage curing agent A, 0.3 g of urotropine first-stage curing agent B and 74.3 g of water, and stir slowly at 10 r / min for 10 min to form a sealing and carbon fixation solution, which is an integrated system of CO2 oil flooding sealing and in-situ curing 5.

[0061] Example 6

[0062] A CO2 flooding sealing and in-situ solidification integrated system, the preparation method is as follows:

[0063] (1) Add 1g of stabilizer to 99g of water and stir mechanically at 500r / min for 6h to form a stabilizer solution. The stabilizer is polymerized by acrylamide and sodium 2-acrylamido-2-methylpropanesulfonate in a molar ratio of 18:1.

[0064] (2) Add 4 g of choline chloride and 6 g of urea into 90 g of water, maintain mechanical stirring at 500 r / min, and stir for 10 min to obtain a second-stage curing agent solution;

[0065] (3) Mix 10 g of stabilizer solution, 15 g of second-stage curing agent solution, 0.05 g of sodium dodecyl sulfate foaming agent, 0.3 g of amphiphilic carbon quantum dot foaming enhancer, 0.25 g of resorcinol first-stage curing agent A, 0.3 g of urotropine first-stage curing agent B and 74.1 g of water, and stir slowly at 10 r / min for 10 min to form a sealing and carbon fixation solution, which is an integrated system of CO2 oil flooding sealing and in-situ curing 6.

[0066] Example 7

[0067] A CO2 flooding sealing and in-situ solidification integrated system, the preparation method is as follows:

[0068] (1) Add 4g of stabilizer to 96g of water, maintain mechanical stirring at 500r / min, and stir for 6h to form a stabilizer solution. The stabilizer is polymerized by acrylamide and sodium 2-acrylamido-2-methylpropanesulfonate in a molar ratio of 10:1.

[0069] (2) Add 4 g of choline chloride and 6 g of urea into 90 g of water, maintain mechanical stirring at 500 r / min, and stir for 10 min to obtain a second-stage curing agent solution;

[0070] (3) Mix 10 g of stabilizer solution, 15 g of second-stage curing agent solution, 0.05 g of sodium dodecyl sulfate foaming agent, 0.3 g of amphiphilic carbon quantum dot foaming enhancer, 0.15 g of resorcinol first-stage curing agent A, 0.25 g of urotropine first-stage curing agent B and 74.25 g of water, and stir slowly at 10 r / min for 10 min to form a sealing and carbon fixation solution, which is an integrated system of CO2 oil flooding sealing and in-situ curing7.

[0071] Example 8

[0072] A CO2 flooding sealing and in-situ solidification integrated system, the preparation method is as follows:

[0073] (1) Add 4g of stabilizer to 96g of water, maintain mechanical stirring at 500r / min, and stir for 6h to form a stabilizer solution. The stabilizer is polymerized by acrylamide and sodium 2-acrylamido-2-methylpropanesulfonate in a molar ratio of 10:1.

[0074] (2) Add 4 g of choline chloride and 6 g of urea into 90 g of water, maintain mechanical stirring at 500 r / min, and stir for 10 min to obtain a second-stage curing agent solution;

[0075] (3) Mix 10 g of stabilizer solution, 10 g of second-stage curing agent solution, 0.05 g of sodium dodecyl sulfate foaming agent, 0.3 g of amphiphilic carbon quantum dot foaming enhancer, 0.25 g of resorcinol first-stage curing agent A, 0.3 g of urotropine first-stage curing agent B and 79.1 g of water, and stir slowly at 10 r / min for 10 min to form a sealing and carbon fixation solution, which is an integrated system of CO2 oil flooding sealing and in-situ curing8.

[0076] Comparative Example 1

[0077] On the basis of Example 2, in step (3), the component: amphiphilic carbon quantum dot foaming enhancer is removed, and finally a solution without foaming enhancer is obtained, namely, comparative solution system 1.

[0078] Comparative Example 2

[0079] On the basis of Example 2, the component: stabilizer is removed, and finally a solution without stabilizer is obtained, namely, comparative solution system 2.

[0080] Comparative Example 3

[0081] On the basis of Example 2, in step (1), the stabilizer used is prepared by polymerization of acrylamide and sodium 2-acrylamido-2-methylpropanesulfonate in a molar ratio of 20:1, and finally a comparative solution system 3 is obtained.

[0082] Comparative Example 4

[0083] On the basis of Example 2, the two components of the first-stage curing agent A and the first-stage curing agent B were removed, and finally a solution containing no first-stage curing agent was obtained, namely, comparative solution system 4.

[0084] Comparative Example 5

[0085] On the basis of Example 2, the component: the second-stage curing agent is removed, and finally a solution without the second-stage curing agent is obtained, namely, comparative solution system 5.

[0086] Comparative Example 6

[0087] On the basis of Example 2, the choline chloride content in the second-stage curing agent was increased, that is, in step (2), 8 g of choline chloride and 2 g of urea were used, and finally a comparative solution system 6 was obtained.

[0088] The performance tests of the solution systems prepared in the above Examples 1-8 and Comparative Examples 1-6 are as follows:

[0089] 1. Evaluation of foaming performance and foam stability of solution system

[0090] The foaming performance and foam stability tests were conducted using the solutions prepared in Examples 1 to 7 and Comparative Examples 1 to 4. Test method: Each solution to be tested was stirred at 8000 r / min for 5 min using a Waring stirrer to form foam, and the foam was placed in a stoppered measuring cylinder, and the initial foam volume was recorded. Subsequently, the entire stoppered measuring cylinder was placed in a DHG-9140A oven and aged at 80°C for 30 days, and the change in foam volume and the amount of precipitated liquid were recorded. The experimental results are shown in Table 1.

[0091] The experimental data in Table 1 show that the initial foam volume and the foam volume after 30 days of Examples 1 to 4 are both over 500 ml, and the precipitated liquid volume is all below 10 ml. This indicates that the CO2 flooding sealing and in-situ curing integrated system prepared in Examples 1 to 4 has excellent foaming properties and the generated foam has strong stability.

[0092] Compared with Example 4, the amount of foaming synergist added in Example 5 was reduced from 0.3% to 0.1%, and the initial foam volume of Example 5 was reduced by 37.08% compared with the initial foam volume of 836 ml generated in Example 4. Compared with Example 2, no foaming synergist was added in Comparative Example 1, and the initial foam volume of Comparative Example 1 was reduced by 67.01% to only 324 ml compared with the initial foam volume of 982 ml generated in Example 2. This result proves that the addition of the foaming synergist not only improves the foaming ability of the solution system, but also greatly enhances the mechanical properties of the foam liquid film.

[0093] Compared with Example 4, the amount of first-order curing agent A added in Example 7 is reduced from 0.25% to 0.15%, and the amount of first-order curing agent B added is reduced from 0.3% to 0.25%. Compared with Example 2, first-order curing agent A and first-order curing agent B are not added in Comparative Example 4. After 30 days of aging treatment, the foam volume reduction in Example 7 is increased by 30.8% compared with that in Example 4, and the amount of precipitated liquid is increased by 28.2 ml. Compared with Example 2, the foam volume reduction in Comparative Example 4 is increased by 63.75%, and the amount of precipitated liquid is increased by 62.9 ml. This result proves that under the joint action of first-order curing agent A and first-order curing agent B, the mechanical strength of the integrated system of CO2 oil flooding sealing and in-situ curing after gelation can be greatly improved, and the stability of the foam can be enhanced.

[0094] Compared with Example 4, the amount of stabilizer added in Example 6 was reduced from 0.4% to 0.1%, and the molar ratio of acrylamide to sodium 2-acrylamido-2-methylpropanesulfonate in the stabilizer was increased from 10:1 to 18:1. In Example 6, the relative content of acrylamide increased, the molecular weight of the copolymer formed decreased, and the amount of stabilizer added decreased, the gelling effect became worse, and the stability of the liquid film weakened, resulting in an increase of 29.48% in the foam volume reduction after 30d aging treatment compared with Example 4, and an increase of 23.6ml in the amount of precipitated liquid.

[0095] Compared with Example 2, no stabilizer was added in Comparative Example 2, and the molar ratio of acrylamide to 2-acrylamido-2-methylpropanesulfonate of the stabilizer added in Comparative Example 3 exceeded the preferred range. After 30 days of aging treatment, the foam volume reduction of Comparative Example 2 increased by 60.65% compared with that of Example 2, and the amount of precipitated liquid increased by 59.2 ml; the foam volume reduction of Comparative Example 3 increased by 49.46% compared with that of Example 2, and the amount of precipitated liquid increased by 48.4 ml. Comparative Example 2 lacks the necessary stabilizer, and its liquid film cannot undergo cross-linking reaction to form gel, resulting in a significant weakening of the foam stability. After 30 days of aging treatment, a large amount of foam ruptures. The relative content of acrylamide in the stabilizer added in Comparative Example 3 exceeds the preferred range, and the molecular weight of the stabilizer formed is reduced, resulting in the difficulty of maintaining the stability of the foam after gelation. This result shows that after the stabilizer in the liquid film undergoes cross-linking reaction with the first-order curing agent, the formation of a gel with a certain mechanical strength can greatly improve the stability of the liquid film.

[0096] Table 1 Foaming performance and stability performance of different systems prepared in Examples and Comparative Examples

[0097]

[0098] 2. Evaluation of Plugging Capacity

[0099] The artificial sand-filled pipe displacement physical model was used to test the plugging capacity of different CO2 oil flooding plugging and in-situ solidification integrated systems. The sand-filled pipe size used in the test was φ3.8cm×30cm, and the sand-filled medium was 40~60 mesh quartz sand. The gas used in the test process was CO2, the CO2 injection rate was set to 0.5ml / min, the system injection rate was 0.3mL / min, and a total of 0.5PV system was injected. The test method steps are as follows:

[0100] (1) Load the sand filling medium into the sand filling tube and press Figure 2The experimental device is connected as shown, one end of the sand-filling pipe is connected to three intermediate containers in parallel at the same time, a piston is arranged in the intermediate container to divide the internal space into two upper and lower chambers, the upper chambers of the three intermediate containers store water, injection and sealing carbon fixation solution and CO2 respectively, the lower chambers of the three intermediate containers are connected to a constant flow pump, water is injected into the lower chamber through the constant flow pump to push the piston to move upward, and then water, injection and sealing carbon fixation solution or CO2 are injected into the sand-filling pipe; the other end of the sand-filling pipe is connected to a back pressure valve, and the back pressure valve is connected to a constant pressure pump; after the experimental device is connected, the sand-filling pipe is subjected to a gas measurement porosity and permeability experiment;

[0101] (2) Using the gas-water alternating injection method, first inject 0.1PV of sealing and carbon fixation solution into the sand filling pipe, then inject 0.1PV of CO2, and cycle alternately for 5 times;

[0102] (3) The sand-filled tube was placed in an oven at 80°C for 10 h for cross-linking reaction, and then CO2 flooding was performed until the pressure was stable. The permeability and plugging rate after plugging were calculated.

[0103] The experimentally measured permeability of the sand-filled pipe before and after displacement and the plugging rates of different embodiments and comparative examples are shown in Table 2:

[0104] Table 2 The plugging capacity of different sealing and carbon fixation solutions

[0105]

[0106] As can be seen from Table 2, the plugging rates of Examples 1 to 7 are all above 82%, which proves that the sealing and fixing carbon solution of the present invention has a good plugging effect and can effectively increase the swept volume of CO2 flooding. After the sealing and fixing carbon solution and CO2 are alternately injected, the sealing and fixing carbon solution and CO2 exist in the form of foam through the shearing action of the porous medium, and rely on the Jamin effect to plug the dominant channel. The copolymer in the subsequent liquid film undergoes a cross-linking reaction to form a three-dimensional network structure with gel as the external phase to form a foam skeleton, which greatly improves the stability of the foam, thereby more effectively plugging the dominant channel.

[0107] Compared with Example 2, no foaming synergist was added in Comparative Example 1, and its plugging rate decreased by 34.46%. After the solution prepared in Comparative Example 1 was alternately injected to form foam, the liquid film lacked a carbon quantum dot nano-ion protective layer, which on the one hand made the mechanical strength of the liquid film deteriorate, and on the other hand made more foam ruptures and disproportionation during the gelation process, which resulted in a poor plugging effect of the foam gel prepared in Comparative Example 1. Compared with Example 2, no stabilizer was added in Comparative Example 2, and its plugging rate decreased by 58.04%. No first-order curing agent A and first-order curing agent B were added in Comparative Example 4, and its plugging rate decreased by 63.09%. Due to the lack of necessary gelling substances in Comparative Examples 2 and 4, when the solution and CO2 formed foam under the shearing action of the porous medium, the copolymer in the liquid film could not undergo a cross-linking reaction to form a three-dimensional network gel, which greatly attenuated the stability of the foam, and thus the plugging ability was greatly reduced. This indicates that the sealing and carbon-fixing solution of the present invention can produce a strong blocking effect on the dominant channels in the formation only under the combined action of the adsorption of the foaming synergist and the gelation of the copolymer in the liquid film.

[0108] 3. Evaluation of curing ability

[0109] The solidification ability test was carried out using the sealing and fixing carbon solutions prepared in Example 2, Example 3, and Example 8, and the comparative solutions prepared in Comparative Example 1, Comparative Example 2, Comparative Example 4, Comparative Example 5, and Comparative Example 6. The test steps are as follows:

[0110] (1) CO2 was introduced into each test solution, and agitated at 8000 r / min for 5 min using a Waring stirrer to form foam, and the foam was sealed in a stoppered measuring cylinder and placed in an oven at 80°C for 5 h to form a foam gel with CO2 as the gas phase;

[0111] (2) The prepared foam gel was taken out and soaked in simulated formation water at a constant temperature of 80°C for 30 days; the formula of the simulated formation water is shown in Table 3;

[0112] (3) Remove the foam gel and rinse with distilled water;

[0113] (4) drying the foam gel in an oven at 50°C and grinding it into powder;

[0114] (5) Washing, filtering, drying and weighing the powder;

[0115] (6) The dried powder was acid-washed and filtered with 5% by volume HCl, washed three times with water, dried, and weighed to calculate the solidified amount.

[0116] Table 3 Composition of simulated formation water

[0117]

[0118] The curing amount of different foam gels was statistically analyzed, and the results are shown in Table 4.

[0119] Table 4 Different Foam Gel Curing Amounts

[0120]

[0121] As shown in Table 4, the solidification amount of the sealing and fixing carbon solution prepared in Examples 2, 3, and 8 within 30 days is all above 0.45g, which proves that the sealing and fixing carbon solution prepared can effectively convert CO2 into solid carbonate in the formation environment. Compared with Example 2, no foaming synergist was added in Comparative Example 1, and the gas phase content in the generated foam gel was significantly reduced; no stabilizer was added in Comparative Example 2, and no first-order curing agent was added in Comparative Example 4, the long-term stability of the foam was weakened, and more foams broke during the second-order curing process, resulting in a reduction in the amount of CO2 that actually underwent mineralization reaction. Therefore, the solidification amount of Comparative Examples 1, 2, and 4 was significantly lower than that of Example 2. Compared with Example 2, no second-order curing agent was added in Comparative Example 5. Although a small amount of solid carbonate was generated, due to the lack of the necessary second-order curing agent, the divalent metal cations in the simulated formation water were difficult to contact with the CO2 in the foam, which seriously slowed down the conversion rate of free CO2 to solid carbonate. Compared with Example 2, the content of choline chloride in the second-stage curing agent added in Comparative Example 6 exceeds the preferred range. The increase of choline chloride means that more positive charges are introduced into the solvent, resulting in an increase in charge density, thereby increasing the electrostatic repulsion between ions and reducing the migration rate of ions. Therefore, the curing amount in Comparative Example 6 is much lower than that in Example 2 in the same time.

[0122] The above description is only a preferred embodiment of the present invention and does not constitute any form of limitation to the present invention. Although the present invention has been disclosed as a preferred embodiment as above, it is not intended to limit the present invention. Any technician familiar with the profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.

Claims

1. A CO2 flooding sealing and in-situ solidification integrated system, characterized in that: Made from the following raw material components in weight percentage: 0.05%~0.10% foaming agent, 0.1%~0.5% foaming synergist, 0.1%~0.8% stabilizer, 0.15%~0.30% first-stage curing agent A, 0.25%~0.35% first-stage curing agent B, 1.0%~2.0% second-stage curing agent, and the rest is water, all components total 100%; Wherein, the foaming agent is one or a combination of sodium alkylbenzene sulfonate and sodium dodecyl sulfate; The foaming synergist is amphiphilic carbon quantum dots; the amphiphilic carbon quantum dots are prepared by the following method: (1) Mix dodecylamine and citric acid and stir at 180°C for 5 h; (2) dissolving the product of step (1) in anhydrous ethanol, centrifuging and removing insoluble matter in the product; (3) The product was dissolved in deionized water, dialyzed with a 1 kDa dialysis membrane for 12 h, and finally freeze-dried to obtain amphiphilic carbon quantum dots; The stabilizer is a copolymer of acrylamide and sodium 2-acrylamide-2-methylpropane sulfonate, the molecular weight of the copolymer is 1 million to 8 million; the molar ratio of acrylamide to sodium 2-acrylamide-2-methylpropane sulfonate is 7:1 to 18:1; the preparation method is as follows: Dissolve acrylamide and sodium 2-acrylamido-2-methylpropane sulfonate in water according to a preferred molar ratio, then add an appropriate amount of sodium hydroxide to adjust the pH value of the solution to neutral, add an appropriate amount of ammonium persulfate to the solution to fully dissolve, react at 60°C for 4 hours, take out the product, dry it, and grind it to obtain a powdery product, wherein the total mass of acrylamide and sodium 2-acrylamido-2-methylpropane sulfonate accounts for 20% of the total mass fraction of the reaction system, and the amount of ammonium persulfate accounts for 0.05% to 0.1% of the total mass of acrylamide and sodium 2-acrylamido-2-methylpropane sulfonate; The first-stage curing agent A is resorcinol or hydroquinone; The first-stage curing agent B is hexamethylenetetramine; The second-stage curing agent is a composition of choline chloride and urea. Based on 100% of the total amount of choline chloride and urea, the mass percentage of choline chloride is 30%-50%, and the mass percentage of urea is 50%-70%.

2. A method for preparing the integrated system of CO2 flooding sealing and in-situ curing as claimed in claim 1, characterized in that: Here are the steps: (1) Dissolving the stabilizer in water to form a stabilizer solution; (2) dissolving the second-stage curing agent in another portion of water to form a second-stage curing agent solution; (3) The stabilizer solution, the second-stage curing agent solution, the foaming agent, the foaming enhancer, the first-stage curing agent A, the first-stage curing agent B and the remaining water are mixed and slowly stirred at a speed of 8-12 r / min for 8-10 minutes to form a sealing and carbon fixation solution, which is an integrated system of CO2 oil flooding sealing and in-situ solidification.

3. An application method of the integrated system of CO2 oil flooding sealing and in-situ solidification as claimed in claim 1, characterized in that: The integrated system of CO2 oil flooding sealing and in-situ solidification is injected into the reservoir alternately with CO2.

Citation Information

Patent Citations

  • A CO2-responsive in-situ gel sealing agent, its preparation method and application

    CN107556996B

  • Foaming sealants for CO2 flooding in heavy oil reservoirs, their preparation methods and applications

    CN111139051B

  • Foam profile control system suitable for advanced profile control of oilfield and preparation method of foam profile control system

    CN104152126A

  • Foam auxiliary carbon dioxide throughput oil production method

    CN106811188A